2016
DOI: 10.1007/978-3-319-50106-2_28
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Practicality of Maximal Planar Subgraph Algorithms

Abstract: Given a graph G, the NP-hard Maximum Planar Subgraph problem (MPS ) asks for a planar subgraph of G with the maximum number of edges. There are several heuristic, approximative, and exact algorithms to tackle the problem, but-to the best of our knowledgethey have never been compared competitively in practice. We report on an exploratory study on the relative merits of the diverse approaches, focusing on practical runtime, solution quality, and implementation complexity. Surprisingly, a seemingly only theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Instead, a sufficiently large but in many practical cases small subset of constraints is identified by a (heuristic) separation procedure. Over the years, the performance of this approach was improved by strong preprocessing [7], finding multiple violated constraints in linear time [12], and good heuristics [11].…”
Section: Known Formulation: Kuratowski Subdivisionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, a sufficiently large but in many practical cases small subset of constraints is identified by a (heuristic) separation procedure. Over the years, the performance of this approach was improved by strong preprocessing [7], finding multiple violated constraints in linear time [12], and good heuristics [11].…”
Section: Known Formulation: Kuratowski Subdivisionsmentioning
confidence: 99%
“…In addition, we generated a set of random regular [29] graphs that are expander graphs with high probability. In [11] it was observed that such graphs seem to be especially hard at least for the Kuratowski formulation. For formulations that allow multiple configurations, we determined the most promising one in a preliminary benchmark on a set of 1224 Rome and North graphs, as reported in the previous sections.…”
Section: :10mentioning
confidence: 99%
See 1 more Smart Citation
“…Still, since it has these guarantees on integral solutions, it suffices to obtain an exact algorithm. Over the years, the performance of this approach was improved by strong preprocessing [4], finding multiple Kuratowski subdivision in linear time [11], and strong primal heuristics [10]. We use all these identically in all considered algorithms.…”
Section: Kuratowski Model (ε-Model)mentioning
confidence: 99%
“…There are several practical heuristic approaches to tackle the problem [10]. However, MPS is MaxSNP-hard, i.e., there is an upper bound < 1 on the obtainable approximation ratio unless P = NP [2], and there are further limits known for specific algorithmic approaches [3,7].…”
Section: Introductionmentioning
confidence: 99%